ответ:Решение:
y=log_2(x^2-9)
D: x^2 - 9 > 0
(x - 3)(x + 3) > 0
+___(-3)___-___(3)___+___x
x Є (- ∞ ; - 3) U (3; + ∞ )
ответ: D = (- ∞ ; - 3) U (3; + ∞ ) где-то так точно не уверен
Объяснение:
у=log2(x^2-9)
x²-9>0
(x-3)(x+3)=0
x= 3; -3
x∈(-∞;-3)∪(3;+∞)
ответ:Решение:
y=log_2(x^2-9)
D: x^2 - 9 > 0
(x - 3)(x + 3) > 0
+___(-3)___-___(3)___+___x
x Є (- ∞ ; - 3) U (3; + ∞ )
ответ: D = (- ∞ ; - 3) U (3; + ∞ ) где-то так точно не уверен
Объяснение:
у=log2(x^2-9)
x²-9>0
(x-3)(x+3)=0
x= 3; -3
x∈(-∞;-3)∪(3;+∞)